L2-constructions that go together – more on valency constructions and learner language - Garibyan, Armine; Balog, Evelin; Herbst, Thomas (Yearbook of the German Cognitive Linguistics Association, 2019)
This paper sets out to illustrate differences between learner language and the language of native speakers by a number of tests carried out with students of English at the Friedrich-Alexander-Universität Erlangen-Nürnberg. The first part of the experiment aims at testing knowledge of collocations: In order to compare to what extent combinations of certain words are stored in the constructica of native speakers and advanced learners of English, we used the test battery developed by Dąbrowska (2014): although, as was to be expected, on the whole, native speakers displayed a much greater competence at judging which combinations of words can be regarded as established collocations, interestingly, some learners outperformed some native speakers. The second part of the project was designed to explore the number and types of different valency constructions informants produce on being provided with a verbal stimulus. It is very interesting to see that, given the stimulus word caught, for example, the non-native speakers would predominantly produce sentences with police, thief, murderer, suspect etc. which do not rank amongst the 50 top collexemes of caught in the British National Corpus. We would thus argue that an analysis of the words used in particular slots of argument structure constructions (i.e. the collexemes or itecxes) provides a useful means of characterizing the language of advanced learners and to underscore the importance of collo-phenomena in language teachin
Keywords: collocation; construction; pattern; valency; learner language